Etos Kerja Wanita Pedagang Acung dan KebertahananNilai-Nilai Sosial-Ritual di Kalangan Masyarakat Bali - Parmiti, Desak Putu (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2017)
Target of this research is to identify and formulate of free-merchant woman work ethos at central of tourism area in Bali and to know relation among ethos work of free-merchant woman with socio-culture conflict. This Research used approach "Critical Etnography Research" in research paradigm qualitative. Research data collected by using partisipative observation, interview, quitionaire, and document studies. Overall of research data a nalysed by using technique analyse qualitative with analysis model pass by dots-quickly.Result of research indicate that: (1) all of free-merchant woman in Bali have typical of activity ethos and have the open character, (2) there are bearing having the character of magic-logical among ethos work of all free-merchant woman in Bali with friction of local socio-culrure, (3) patterned thinking and behavior of all free-merchants woman give very positive contribution to construction effort and added values for existention of Balines society.